Implementation of distributed control of hierarchical assembly systems via extended critical places - Yang, Yan (2021)
Deadlock problem, a research area full of vitality, has been extensively investigated in the framework of Petri nets. Much of the work on deadlock problem mainly focuses on the models with flexible routes, while there are few theoretical results from the models with assembly operations, especially the models with hierarchical assembly operations. In this paper, an innovative distributed control method for assembly systems with complex structures is developed. Before advancing to the next step, a forward search procedure is conducted on the concerned process to check whether there exists a firing sequence from its current place to its nearest global critical place. The movement of its next step is allowed when the search result is positive; otherwise, our method prohibits its one-step movement and the same search method is imposed on the remaining processes until a positive result is returned. During the execution of our control method, because of no demanding of all the states and communication with other unchecked processes, a great reduction of computational complexity can be achieved with our on-line and real-time control strategy.